Edgeloop character modeling for 3D professionals only. - Murdock, Kelly L., ....-; Allen, Eric M., ....- (Hoboken : Wiley, 2006)
Edgeloop modeling is a revolutionary feature added to the latest releases of 3ds Max, Maya, LightWave, and SoftImage that allows animators to create lifelike characters that move realistically without gaps, wrinkles, or deformities This full-color book walks readers through the process of creating an action hero reminiscent of Lara Croft in Tomb Raider Bestselling author Kelly Murdock first explains the key concepts of edgeloop modeling and examines how it differs from other methods Readers learn how to customize a torso, add extremities, model the head and face, and finally add jewelry, weapons, and other details A CD-ROM includes all the examples from the book and a collection of other models
Keywords: Tekenkunst